THE SYNTAX-MORPHOLOGY INTERFACE: HOW WORD STRUCTURE INFLUENCES SENTENCE CONSTRUCTION - Zhafran Fatih Ananda; Dwi Syukriady; Rusdi Room; Linda Fitriyanti; Pahar Kurniadi; Lulu Jola Uktolseja (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
This study explores the syntax-morphology interface, focusing on how internal word structure influences sentence construction across languages. It investigates the ways in which morphological processes—such as affixation, reduplication, and inflection—interact with syntactic behavior, shaping how words function within phrases and sentences. Drawing from theoretical frameworks and cross-linguistic data, the analysis reveals that word form is not merely an internal or isolated phenomenon, but one that plays a crucial role in determining grammatical relations, argument structure, and agreement patterns. For instance, morphological variations in verb forms can directly affect subject-object positioning and syntactic valency. These findings underscore the interdependence between morphology and syntax, suggesting that a comprehensive understanding of one requires close attention to the other. This research contributes to the refinement of generative linguistic theory and offers insights into the typological diversity of language structure.